A Multi-Objective Approach for Optimizing Aisle Widths in Underground Parking - Igor Kabashkin; Alua Kulmurzina; Assel Zhandarbekova; Zura Sansyzbayeva; Timur Sultanov (Infrastructures)
This study presents a multi-objective optimization approach for determining optimal aisle widths in underground parking facilities, balancing vehicle maneuverability against parking capacity. The research methodology integrates geometric modeling, computational simulations, and empirical validation to establish evidence-based recommendations for aisle width design. Through systematic testing of aisle widths ranging from 4.5 to 6.0 m across various vehicle types, the study identifies 5.0–5.5 m as the optimal range that maximizes both objectives for modern vehicle fleets. Geometric modeling establishes theoretical minimum widths based on vehicle turning radii, while software simulations quantify maneuverability metrics including parking success rates, time requirements, and collision probabilities. Physical testing in operational underground parking facilities validates these findings through controlled experiments with drivers of varying experience levels. The research demonstrates that aisle widths below 5.0 m significantly compromise maneuverability, particularly for larger vehicles, while widths exceeding 5.5 m provide negligible additional benefits while reducing capacity. A case study application in Kazakhstan, examining regional vehicle distributions and regulatory frameworks, confirms the model’s practical utility. The findings suggest that current parking standards in some regions may require revision to accommodate changing vehicle dimensions. This optimization framework provides urban planners, architects and engineers with a data-driven methodology for designing underground parking facilities that enhance both user experience and space utilization efficiency.